Sustainable development as a source of competitive advantiage: An empirical research study in museums - Izabela Luiza Pop; Rada Florina Hahn; Corina Michaela Radulescu (UTMS Journal of Economics, 2018)
Worldwide organisations are continually searching for new sources of competitive advantage. At the same time, they are under increasing pressure to carry out their activities so as not to harm the environment in addition to having a positive impact on society. Given these facts, our paper analyses whether, and under what conditions, sustainable development could be an opportunity rather than a threat for organisations. In particular, the research focuses on investigating a possible link between sustainable development and museums' competitiveness. In order to achieve this goal, after an in-depth study of the literature, we distributed and collected surveys from 87 museums of different sizes, types, and importance from all Romanian development regions. Subsequently, we used Spearman's correlation coefficient to test the statistical hypotheses. The findings indicate that both social and environmental pillars of sustainability have positive links with the economic performance of a museum. Our research highlights that not only private companies but also non-profit organisations, such as museums, can use sustainable development to improve their economic results and, in this way, to achieve higher levels of competitiveness. Therefore, the findings of this study are helpful for all organisations wishing to determine how sustainable development can be turned into a tool for enhancing competitiveness.
Keywords: M10; M14; O44; Q01; 330; competitiveness; strategy; economic performance; environment; social responsibility